2021
DOI: 10.1542/peds.2020-021204
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Lung Inflations During Neonatal Resuscitation at Birth: A Meta-analysis

Abstract: CONTEXT: The International Liaison Committee on Resuscitation prioritized review of sustained inflation (SI) of the lung at birth. OBJECTIVE: To complete a systematic review and meta-analysis comparing strategies using 1 or more SI ≥1 second with intermittent inflations <1 second for newborns at birth. DATA SOURCES: Medline, Embase, and Evidence-Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…SI as initial respiratory support in the DR has been postulated to achieve a more unified lung aeration [44]. However, recent systematic reviews reported similar rates of bronchopulmonary dysplasia when SI was compared with intermittent positive pressure ventilation for initial respiratory support in the DR [45,46]. These reviews also reported that in a subgroup of <28 weeks' gestation, SI was associated with potential increased risk of death before discharge (risk ratio 2.42 (95% confidence interval = 1.15-5.09)) and increased risk of death within the first 2 days (risk ratio 1.38 (95% confidence interval = 1.00-1.91)), when compared to intermittent positive pressure ventilation [45,46].…”
Section: Duration Of Sustained Inflationsmentioning
confidence: 99%
See 1 more Smart Citation
“…SI as initial respiratory support in the DR has been postulated to achieve a more unified lung aeration [44]. However, recent systematic reviews reported similar rates of bronchopulmonary dysplasia when SI was compared with intermittent positive pressure ventilation for initial respiratory support in the DR [45,46]. These reviews also reported that in a subgroup of <28 weeks' gestation, SI was associated with potential increased risk of death before discharge (risk ratio 2.42 (95% confidence interval = 1.15-5.09)) and increased risk of death within the first 2 days (risk ratio 1.38 (95% confidence interval = 1.00-1.91)), when compared to intermittent positive pressure ventilation [45,46].…”
Section: Duration Of Sustained Inflationsmentioning
confidence: 99%
“…Recently, the SAIL trial compared SI with intermittent positive pressure ventilation in < 28 weeks' gestation infants and reported an increased mortality within the first 48 h with SI [67]. Most recently, a meta-analysis from ILCOR raised concerns about the potential harm of SI for premature infants < 28 weeks' gestation [46]. These data raise some concerns about the use of SI during the initial respiratory support.…”
Section: Limitationsmentioning
confidence: 99%
“…The European resuscitation guidelines recommend "five inflations maintaining the inflation pressure for up to 2-3 s" [6], while the North American resuscitation guidelines recommend PPV [5]. Several trials comparing sustained inflations, in which an inflating pressure is held for a prolonged duration greater than 5 s with PPV demonstrated no differences in the primary outcome of death before hospital discharge or secondary outcome parameters [56][57][58]. The SAIL trial, which enrolled 426 infants (23 to 26 weeks' gestation), was terminated early due to a higher rate of death within the first 48 h of life in the sustained inflation group.…”
Section: Initial Respiratory Supportmentioning
confidence: 99%
“…(63)(64)(65)(66)(67)(68)(69) However, a recent systematic review showed no difference in the primary outcome of death before discharge (RR 1.09, 95% CI 0.83-1.43) as well as other pre-specified critical outcomes. (70)(71)(72) A large randomised controlled trial was terminated early owing to increased early death in newborns with gestational age < 29 weeks who were randomised to SLI (RR 2.42, 95% CI 1.15-5.09). (73)…”
Section: Rate and Inspiratory Time During Ppvmentioning
confidence: 99%